Feasibility of closed ventilation and automatic ventilation for sea freight of Proteaceae cut flower stems - Matsikidze, Stenford Ngonidzashe (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.